Dampak Sosial Budaya Pengembangan Dusun Sade Sebagai Dusun Wisata Di Kabupaten Lombok Tengah - Nur Kumala Sari; Saptono Nugroho (JURNAL DESTINASI PARIWISATA, 2018)
Sade is one of tourism villages located in Sub-district of Pujut, Central Lombok Regency. The development of the tourism village in Sade has given many impacts such as socio-cultural impact. The community of Sasak Tribe in Sade depends on globalization. It caused the intensive communication between Sade’s community with tourist and people around. The community can not decline the tourism development which offer many economically advantages. The method of this research using qualitative approach. This research uses both qualitative and quantitative data which collect by observation, interview and documentation. The informant chosen by procedure purposive method. In this report data will display by description and table. The parameter of this research is limited by concept socio-cultural impact, culture and tourism village. The results of this research shows the socio-cultural condition of Sade’s community before becoming as a tourism village is stable. They have being impacted mundane in agriculture sector and local organization. Local language is used in their daily life. However, after being a torism village there is complexity livelihood transformation from agricultural to tourism sector. Some new organizations appear such us Kelompok Sadar Wisata (Pokdarwis) and the local manager of Sade Tourism Village. The other impact is the community use foreign languages to communicate with tourist. However, the changes that have taken place shows that Sade’s culture is not weak. Despite the changes but their culture and the local ethnic identity is not affected by tourism activities. Keywords : socio-cultural impact, tourism development, tourism village